2022
DOI: 10.1002/eat.23714
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone status and efficacy of dehydroepiandrosterone supplementation for bone health in anorexia nervosa: A systematic review and meta‐analysis

Abstract: Objective This study was designed to determine the status of dehydroepiandrosterone (DHEA) in women with anorexia nervosa (AN) and to assess the efficacy of DHEA supplementation as a treatment for bone health in women with AN. Method Studies were retrieved from the PubMed, Embase, Cochrane Library, MEDLINE, and Scopus databases from inception to February 14, 2022. Observational studies that compared serum DHEA levels between women with AN and healthy controls were included for meta‐analysis, and randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…However, previous studies on DHEA in blood samples in AN have obtained heterogeneous results, which may be in line with the null hypothesis. These results were summarized in a recently published review and meta-analysis [ 15 ]. The authors concluded that DHEA concentrations may be elevated in AN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies on DHEA in blood samples in AN have obtained heterogeneous results, which may be in line with the null hypothesis. These results were summarized in a recently published review and meta-analysis [ 15 ]. The authors concluded that DHEA concentrations may be elevated in AN.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported decreased [ 9 , 10 ], elevated [ 11 , 12 ] as well as normal DHEA concentrations in blood samples [ 13 , 14 ]. However, a recently published meta-analysis of selected studies concluded that elevated blood levels of DHEA are present in AN [ 15 ]. The heterogeneity of the results of previous studies on DHEA may be partially explained by their relatively small sample sizes, risks of confounding bias (i.e., alcohol consumption, smoking, BMI) as well as the applied measurement methods based on blood, saliva, and urine samples.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a major problem throughout the world. Surveys consistently show that people are concerned by weight and its health related implications, and for that most individuals are making a concerted effort to either maintain or lose weight [3] .…”
Section: Introduction Iobesitymentioning
confidence: 99%